Performance of qSOFA score as a screening tool for sepsis in the emergency department - Atul Kumar Tiwari; Nayer Jamshed; Ankit Kumar Sahu; Akshay Kumar; Praveen Aggarwal; Sanjeev Bhoi; Roshan Mathew; Meera Ekka (Journal of Emergencies, Trauma and Shock, 2023)
Introduction: Sepsis is the leading cause of mortality, and various scoring systems have been developed for its early identification and treatment. The objective was to test the ability of quick sequential organ failure assessment (qSOFA) score to identify sepsis and predict sepsis-related mortality in the emergency department (ED). Methods: We conducted a prospective study from July 2018 to April 2020. Consecutive patients with age ≥18 years who presented to the ED with a clinical suspicion of infection were included. Sensitivity, specificity, positive predictive value (PPV), negative predictive values (NPV), and odds ratio (OR) for sepsis related mortality on day 7 and 28 were measured. Results: A total of 1200 patients were recruited; of which 48 patients were excluded and 17 patients were lost to follow-up. 54 (45.4%) of 119 patients with positive qSOFA (qSOFA >2) died at 7 days and 76 (63.9%) died at 28 days. A total of 103 (10.1%) of 1016 patients with negative qSOFA (qSOFA score <2) died at 7 days and 207 (20.4%) died at 28 days. Patients with positive qSOFA score were at higher odds of dying at 7 days (OR: 3.9, 95% confidence interval [CI]: 3.1–5.2, P < 0.001) and 28 days (OR: 6.9, 95% CI: 4.6–10.3, P < 0.001). The PPV and NPV with positive qSOFA score to predict 7- and 28-day mortality were 45.4%, 89.9% and 63.9%, 79.6%, respectively. Conclusion: The qSOFA score can be used as a risk stratification tool in a resource-limited setting to identify infected patients at an increased risk of death.